2019
DOI: 10.1007/978-3-030-11280-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Collaborative Research Center Micro Cold Forming (SFB 747)

Abstract: Micro systems technology is one of the key enabling technologies of the 21st century [Hes03], with increasing relevance due to a general trend towards miniaturisation in many industries. The main boosters for this trend are currently the consumer and communication electronics market and-to a lesser extent-medical technology (especially microfluidic devices, which had a market volume of approx. $2.5B in 2017 [Cle17]). As an example, for the companies organized in the industry association

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Rotary swaging is an incremental precision forging process, which is used to reduce the cross–section of parts with full or hollow sections [ 1 ]. In the process, the diameter of the workpiece is reduced and the material flows simultaneously in axial and radial directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotary swaging is an incremental precision forging process, which is used to reduce the cross–section of parts with full or hollow sections [ 1 ]. In the process, the diameter of the workpiece is reduced and the material flows simultaneously in axial and radial directions.…”
Section: Introductionmentioning
confidence: 99%
“…To visualize the axial material flow in eccentric thread swaging, Ishkina et al [19] developed a special die on which a small cam was manufactured, they found that the pitch of the resulting thread is not constant over the feeding direction, which means an increasing fluctuation of the axial material flow. In the former research [20], rod workpiece with different friction coefficient was investigated in rotary swaging, it was found that the 1 4 radial material from the outer surface is sensitive to friction condition, and that on the center of the axis and the ends of the reduction, the local material flow is most active. However, the research was only based on rod workpiece and only the equivalent plastic strain was investigated instead of the plastic strain components on different directions.…”
Section: Introductionmentioning
confidence: 99%